Nexus : small worlds and the groundbreaking science of networks - Buchanan, Mark. (New York : W.W. Norton, 2002)
Discusses research in "small-worlds" theory, which contends that networks, whether they be social or biological, interact according to a set pattern; and examines the theory's application to such topics as the global economy and the Human Genome Project.
Includes bibliographical references and index.
Booklist.
Choice.
Library Journal.
Adult
Keywords: Causality (Physics); Pattern formation (Physical sciences); Social networks; Interpersonal relations; Nuclear physics; Physical sciences; Physics -- Philosophy; Quantum theory